Application Arbuscular Mycorrhizal Fungi on Desmodium ovalifolium in Post mining Soil - Sri Muryati; Irdika Mansur; Sri Wilarso Budi (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2017)
Mining activities results on environmental degradation and finally on ecosystem damage. Legume cover crop forming symbiosis with beneficial soil microorganism is widely well known to be used for degraded land reclamation such as in post mining area. Desmodium spp. is one of legume cover crop forming symbiosis with arbuscular mycorrhizal fungi (AMF) and rhizobium symbiosis. This study aimed to analyse the growth respond D. ovalifolium that has inoculated AMF from rhizosfer of 4 types of Desmodium spp. There were two factors that are AMF inoculation and media treatment, were applied: with or without inoculation of AMF, and with or without applications of compost. Inoculation of AMF and compost application increased height of O. sumatrana two week after planting (WAP). Single inoculation of AMF into desmodium spp. improved height variables of stem significantly, total biomass, sprout biomass, and number of postule roots as well. Combination of compost and post mining soil had the highest increased in height 2 WAP and roots biomass of Desmodium spp. This research implies that AMF application is an important key for effective methods in improving plant grow in post mining area.